2022
DOI: 10.3389/fbioe.2022.1073063
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma, a biomaterial, for the treatment of anterior talofibular ligament in lateral ankle sprain

Abstract: Background: Because of the rising prevalence of anterior talofibular ligament (ATFL) damage, there is a considerable interest in developing innovative techniques to improve the biological healing response of ATFL. Platelet-rich plasma (PRP) includes several growth factors linked to a favorable healing response, however none of the studies involved both quality evaluation and clinical results to evaluate this treatment.Purpose: To determine the clinical results of PRP injections into the ATFL in lateral ankle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Because of the rising prevalence of ATFL damage, there is a considerable interest in developing innovative techniques to improve the biological healing response of ATFL. 19 In our study, we have found that both PRP plus rehabilitation and rehabilitation alone groups provided significant improvement in subsequent follow ups. However, more statistically significant improvements were seen in PRP plus rehabilitation group when comparing with Rehabilitation alone.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Because of the rising prevalence of ATFL damage, there is a considerable interest in developing innovative techniques to improve the biological healing response of ATFL. 19 In our study, we have found that both PRP plus rehabilitation and rehabilitation alone groups provided significant improvement in subsequent follow ups. However, more statistically significant improvements were seen in PRP plus rehabilitation group when comparing with Rehabilitation alone.…”
Section: Discussionsupporting
confidence: 54%
“…They proposed that PRP might serve as an alternative non-surgical treatment option in LAS in future research, with the potential to prevent the development of CAI and PTOA. Zhang J et al 19 concluded that PRP injection helped relieve early symptoms of LAS, although all patients saw a similar development after 6 months. Naidu A et al 7 conducted a study and gave single dose of PRP along with walking cast application in acute ankle sprains and showed improvement in VAS, FADI and AOFAS score at 6 months.…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al compared different types of injection methods into the tear site of the anterior talofibular ligament (ATFL) and immobilization with immobilization alone in patients with acute lateral ankle sprain (LAS). After treatment, a significant reduction in VAS score and American Orthopedic Foot and Ankle Score (AOFAS) was documented at 6-and 12-month follow-ups [29]. These findings are in line with those achieved by Samra et al, who reported a significant improvement in functional capacity-agility (p = 0.002) and vertical jump (p = 0.001)-and reduction in fear avoidance (p = 0.014) after a single ultrasoundguided PRP administration into the anterior inferior tibiofibular ligament (AITFL) in 10 Rugby Union players within 14 days of MRI-confirmed ankle syndesmosis injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, accurate and early diagnosis of specific ligament injuries may help guide injection therapies. Multiple studies have shown that platelet rich plasma (PRP) injected into the ATFL results in higher reduction in pain and better functional outcomes in the short term (8 to 12 wk); however, no difference is seen in the longer term (6 months) (46,47). Thus, PRP injections may play a role in higher level athletes and result in a quicker return to sport.…”
Section: Clinical Relevance Of This Ultrasound Protocolmentioning
confidence: 99%